Digital Catalysts: SEM Analysis of Technological Infrastructure, Entrepreneurial Ecosystems, and Economic Productivity using World Bank Data - Muhammad Irfan; Zuli Priyanto; Dedi Sulistiyo Soegoto (Lembaga Pengembangan Kinerja Dosen, 2026)
The transition from investment-driven to innovation-driven economies places technological infrastructure at the forefront of macroeconomic development. This study utilizes Structural Equation Modeling (SEM) to analyze the complex causal relationships between technological infrastructure, the entrepreneurial ecosystem, and economic productivity across 179 economies using comprehensive World Bank data. Grounded in Endogenous Growth Theory, we hypothesize that digital infrastructure serves as a critical catalyst for entrepreneurship, which in turn drives higher economic value added and industrial output. To ensure methodological robustness, the study employs a rigorous data pre-processing approach, specifically transforming skewed variables—such as secure internet servers, patent counts, and trademark applications—into their natural logarithms (Ln) to satisfy distributional normality assumptions for linear modeling. Results derived from Jamovi analysis indicate that technological readiness significantly influences entrepreneurial capacity, which acts as a key mediator subsequently impacting GDP per person employed and industrial value added. These empirical findings suggest that policymakers must prioritize strategic digital backbone investments and secure server infrastructure to unlock the full potential of national entrepreneurial ecosystems. By bridging the digital divide, nations can foster an environment conducive to sustainable innovation and long-term economic growth.